Exportação e imobilização de nutrientes e fixação de carbono em pomar de pereiras em plantio adensado e sistema orgânico - Verlindo, Andricia (2012)
Currently the Brazilian production of pear is meaningless in the face of domestic consumption, mainly due to the lack of management technology, but this scenario can be changed through the development of research, especially in the area of production technology. The mineral elements are extremely important for crop production, but their best use depends on the knowledge of plant demands. In this context, an experiment was conducted in 2010 and 2011 in Guarapuava-PR, Brazil, in order to estimate the nutritional needs of pear cultivars ` Cascatense` and `Tenra` on high density planting an organic system. The plants grafted on the rootstock quince `CPP` were planted in September 2004, spaced 4 x 1 m and conducted in central leader with narrow canopy and drip irrigation. The experimental design was in randomized blocks with two treatments (cultivars), five replicates and five plants per plot. At the end of each growing season, in early autumn, it was removed from the soil one plant per plot. Soon after, the pear trees were cut and separated (roots, trunk, branches and leaves), weighed and incubated in a drying chamber with forced-air circulation, until constant weight. Later, The samples were crushed, milled and taken to the Laboratory of Soil and Plant Nutrition from Unicentro, where the mineral analysis were performed. The fruits from 2010/2011 harvest were collected in January 2011 and were also analyzed. For both cultivars, the highest accumulations of the elements N, Ca, Mg e S on permanent parts, were found in the trunk. For P, the branches presented the highest immobilization. For K, there were differences among cultivars, and in the cultivar Tenra the largest quantities were immobilized in the roots and for the cv. Cascatense in the branches. The amounts of N, K and Mg extracted by the fruits cv. Tenra were higher than those from cv. Cascatense. The mineral contents of leaves were different between cultivars. The minimum nutrient amounts of N, P, K, Ca, Mg and S immobilized annually by the permanent parts of the pear trees were, respectively, 13,763.39 g ha?¹, 1,228.38 g ha?¹, 7,197.24 g ha?¹, 819.445 g ha?¹, 2,261.15 g ha?¹ e 1,267.39 g ha?¹. The minimum nutrient amounts of N, P, K, Ca, Mg and S exported by the fruits were, respectively, 913.32 g, 113.32 g, 1,211.72 g, 52.28 g, 65.05 g e 112.52 g, per fruit ton. The minimum amounts of Fe, Cu, Zn and Mn immobilized annually by the permanent parts of the pear trees were, respectively, 376,006.98 mg ha?¹, 45,695.11 mg ha?¹, 30,984.60 mg ha?¹ and 14,794.87 mg ha?¹. The minimum amountos of Fe, Cu, Zn and Mn exported by the fruits were, respectively 1,911.47 mg ha?¹, 1,322.47 mg ha?¹, 2,353.71 mg ha?¹ e 278.73 mg ha?¹. The organic carbon fixed in the stem of pears cultivars Tenra and Cascatense, represents 42% and 50% of total C fixed, respectively. The minimum organic carbon fixed by roots contributed 25% to the total carbon in the orchard. The biomass components of leaves, stem and roots of cv. Cascatense and Tenra were 5,971.87 kg ha?¹ and 3,712.47 kg ha?¹ organic carbon, respectively.